Microcystic Meningiomas: MRI‐Pathologic Correlation. Issue 5 (10th June 2020) - Kulanthaivelu, Karthik; Lanka, Vivek; Chandran, Chitra; Nandeesh, Bevinhalli N.; Tiwari, Sarbesh; Mahadevan, Anita; Prasad, Chandrajit; Saini, Jitender; Bhat, Maya D.; Chakrabarti, Dhritiman; Pruthi, Nupur; Vazhayil, Vikas; et al.
ABSTRACT: Background and Purpose: Microcystic meningiomas (MM) are a distinctive, rare subtype of Grade I meningiomas with limited radiological descriptions. We intend to identify unique imaging phenotypes and seek radiopathological correlations. Methods: Retrospective analysis of histopathologically proven MM was undertaken. Clinicodemographic profiles, imaging, and histopathological characteristics were recorded. Spearman rank correlations among radiological and pathological attributes were performed. Results: Twenty‐eight cases were analyzed (mean age = 45.5 years; M:F = 1:1.54; mean volume = 50.1 mL; supratentorial n = 27). Most lesions were markedly T2 hyperintense (higher than peritumoral brain edema—a unique finding) (89.3%) and showed invariable diffusion restriction, severe peritumoral brain edema (edema index >2 in 64.3%), a "storiform" pattern on T2‐weighted images (T2WI) (75%), reticular pattern on postcontrast T1 (78.6%)/diffusion‐weighted images (DWI) (65.4%), hyperperfusion, T1 hypointensity (84.6%), and absence of blooming on susceptibility‐weighted image (80.9%). Storiform/reticular morphology correlated with large cysts on histopathology ( ρ = .56; P = .005753). Lesion dimension positively correlated with reticular morphology on imaging ( ρ = .59; P = .001173), higher flow voids ( ρ = .65; P = .00027), and greater microcystic changes on histopathology ( ρ = .51; P = .006778). Peritumoral brain edema was higher for lesions demonstrating greater angiomatous component ( ρ = .46; P = .014451). Conclusions: We have elucidated varied neuroimaging features and highlighted pathological substrates of crucial imaging findings of MM. MM ought to be considered as an imaging possibility in an extra‐axial lesion with a marked hypodensity on noncontrast computed tomography, markedly T2‐hyperintense/T1‐hypointense signal, and a storiform/reticular pattern on T2W/GdT1w//DWI.